BLS handbook of methods for surveys and studies - Bureau of Labor Statistics (Washington D.C. : Bureau of Labor Statistics, 1976)
This book contains measures of unemployment insurance laws, occupational employment statistics collected under the Federal-State cooperative program, international prices, an employment cost index, and workers covered by employment benefit plans.
Bulletin 1910
Includes bibliographical references.
gau 19/10/2016
Ref.
Keywords: Labor and laboring classes--Statistical services; Industrial statistics; United States